Overview of Professional Digital Competence of Teachers in the DKI Jakarta Regional Mobilizing Ecce Unit - Lista Apriliani; Awaluddin Tjalla; Lussy Dwiutami (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Information and Communication Technology (ICT) is becoming an inseparable part of human life today. Its use gives hope for the rapid improvement of various aspects of human life, including education. The use of ICT in education can support the achievement of learning outcomes, and mass dissemination of knowledge, improve the quality of learning and accelerate educational services, and strengthen communication and coordination with new people or working groups. This is the background of the school digitization program. The success of school digitalization at least requires the availability of technological devices, internet networks, and teachers' digital competencies. This study aims to determine the level of professional digital competence of teachers in the driving PAUD unit in the DKI Jakarta area. The research method used is quantitative descriptive. The study population is teachers in the driving ECD unit located in DKI Jakarta Province. The sampling technique used was multistage sampling so a sample of 73 people was obtained. Data collection using questionnaires shared via Google Forms. Most respondents were in the East Jakarta area as many as 24 people (32.9%), South Jakarta as many as 23 people (31.5%), the West Jakarta area as many as 17 people (23.3%), and the North Jakarta area as many as 9 people (12.3%). With a working period of 0-10 years as many as 43 people (58.9%). Based on the results of the analysis, it is known that the value of teachers' professional digital competence is seen from three aspects, namely technological proficiency with an average value of 40.42, pedagogical compatibility with an average value of 42.15, and social awareness with an average value of 21.81. Thus, it can be concluded that teachers in the driving PAUD unit in the DKI Jakarta area have mastery of aspects of technological proficiency, pedagogical compatibility, and social awareness is very good.